Auditoría tributaria y su incidencia en el cumplimiento de las obligaciones fiscales de la cooperativa interprovincial de transporte Valencia, cantón Valencia, año 2014 - Lucas Jaramillo, Denisse Karolina. (2015)
This research was conducted in the Interprovincial Cooperative Transport Valencia, a private institution established to provide regular service passenger Interprovincial Transport Bus, activity played since 56 years ago offering a service of the highest quality for those who prefer . It currently has 67 members, has its head office located in the canton Valencia. In order to know the incidence of a tax audit in compliance with the tax obligations of the Cooperative of Transportation, during the fiscal year 2014, analyzing the information provided to it by the accounting department of the data used for the presentation and statement tax which is subject to the Tax Administration. In the investigation and prior to using methods and techniques as well as the interview using internal control questionnaires was determined that the accounting area faces certain risks by poor training, the accountant takes care of everything in this department ie there is no bookkeeper to work with the tasks required area. In this you can see the description of the main tax processes performed in the Cooperative of Transportation compliance testing established that the information has a low degree of reasonableness. Based on the results obtained, as the respective audit Tax Compliance Report where a value to pay for the tax assessment set was performed.